Molecular gas related to the ring nebula RCW 78 around HD 117688 - Cappa, Cristina Elisabet (2008)
We investigate the distribution of the interstellar gas related to RCW 78 based on ^{12}CO(1-0) observations carried out with the SEST telescope and on data belonging to the NANTEN survey. Complementary HI 21-cm line data from the SGPS and radio data at 4.85 GHz were also used. We report the detection of molecular gas having velocities in the range [-56,-33] km/s associated with the western section of RCW 78. The CO emission distribution is compatible with the interpretation that the western section of the nebula originated in the photodissociation and ionization of the molecular gas by the UV photons of the WN7 star HD 117688, which, along with the action of the stellar winds, carved the molecular cloud.